Is There a Role of Pharmacological Treatments in the Prevention or Treatment of Osteonecrosis of the Femoral Head?: A Systematic Review - Lee, Yun Jong (J Bone Metab, 2019)
BACKGROUND: Various pharmacological treatments have been suggested to treat osteonecrosis of the femoral head. However, their practicability remains a controversial issue. METHODS: We systemically reviewed articles published during last 20 years to assess the efficacy and safety of the pharmacological treatments. RESULTS: To date, enoxaparin, statins, bisphosphonates, iloprost and acetylsalicylic acid have been practiced for the treatment of osteonecrosis. However, none of them were proven to be effective by high level studies, and most of them have adverse reactions. CONCLUSIONS: No pharmacological prevention or treatment of osteonecrosis is recommendable at this moment.